Utilization Of Computers As Digital Literacy For Students Of Saifullah An-Nadliyah Namorambe Islamic Boarding School - Khairani, Sumi; Chiuluto, Kalvin; Dafitri, Haida; Aulia, Rachmat; Musa, Masniza Binti; Nurjamiyah, N (LPPM STIKOM Tunas Bangsa, 2024)
AbstractThis program aims to enhance the digital literacy of students at Pondok Pesantren Saifullah An-Nadliyah Namorambe through computer training. The training covers basic computer skills, word processing software, internet use, and ethical social media practices. The method used includes hands-on training and practice, with skills assessment before and after the sessions. The results show that the students have become more proficient in using computers, searching for information, and using social media responsibly. The program also sparked an increased interest in technology among the students. However, challenges such as limited computers, unstable internet access, and a lack of qualified IT instructors remain. Ongoing support from the pesantren, donors, and the local government is crucial. Overall, the program has a positive impact by preparing students for the digital era. Additionally, the program aims to strengthen the institution's international reputation and expand collaboration with foreign institutions. The two-day training in collaboration with Politeknik Sultanah Bahiyah Malaysia (PTSB) is expected to enhance the students' computer skills and establish computer studies as a mandatory subject at the modern pesantren..